Analisis dan Perancangan Sistem Informasi Kasir UMKM Berbasis Website Untuk Mengontrol Penerapan Manajemen Bisnis - Lokesworo; Saruni Dwiasnati; Herfandi (Computer Science Research and Its Development Journal, 2022)
Micro, Small and Medium Enterprises (MSMEs) are increasingly experiencing development in Indonesia. The transaction data process that runs on the Rosereve Esthetic Brand MSMEs is still recorded on the general ledger. The Business process only produces data on sales of goods in raw form, making it difficult to make sales reports per day, weekly and monthly. A website-based cashier information system has been widely implemented to solve this. Therefore, this research will build a website-based cashier information system. This research resulted in a website-based cashier information system with a development method using Agile, Analysis and design using context diagrams and data flow diagrams. There are amount and profit per transaction features on the report page that can be viewed by period and have two users with different access rights. Testing with the black box testing method got the "Success" result. This research is expected to help management control the running Business processes.